Faktor-Faktor Yang Mempengaruhi Wisatawan Dalam Keputusan Pembelian Kuliner Di Angkringan Puncak Bibis Bantul - nugroho, edi (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
Angkringan Puncak Bibis Bantul is one of the culinary tourism spots in Bantul Regency, Yogyakarta that sells various kinds of rural specialties. Starting from an ordinary angkringan which is then crowded with tourists, Angkringan Puncak Bibis Bantul is growing rapidly, of course, this development is influenced by various factors as an attraction for tourists both from product factors, price factors, promotion factors, and location factors. Therefore, researchers are interested in taking the title Factors Influencing Tourists in Culinary Purchase Decisions at Angkringan Puncak Bibis Bantul. This study aims to determine the effect of product, price, promotion, and location on tourists in culinary purchasing decisions at Angkringan Puncak Bibis Bantul and determine the most dominant variables that influence tourists in culinary purchasing decisions at Angkringan Puncak Bibis Bantul. The results show that (1) Product Factors (X1), Price Factors (X2), Promotion Factors (X3), and Location Factors (X4) together have an effect on Tourists in Culinary Purchase Decisions at Angkringan Puncak Bibis Bantul with an value of 18,139>2.47 . (2) Product factor (X1) is not the dominant factor with a value of 3,688 and Location Factor (X4) is the most dominant variable affecting Tourists in Culinary Purchase Decisions at Angkringan Puncak Bibis Bantul with a value of 4,213. R Square of 0.409 which means 40.9% of the Tourist Purchase Decision variable (Y) is influenced by the Product variable (X1), Price variable (X2), Promotion variable (X3), and Location variable (X4), the remaining 59.1% influenced by other variables not discussed in this study.